Pengaruh Disiplin Kerja, Beban Kerja, dan Cyberloafing terhadap Kinerja Pegawai Dinas Pendidikan Kota Kediri - Santi Wilujeng; Heru Sutapa; Indah Yuni Astuti (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This research is motivated by the importance of improving employee performance in the public sector, particularly at the Department of Education of Kediri City, which faces challenges related to work discipline, workload, and the phenomenon of cyberloafing. The study aims to analyze the influence of work discipline, workload, and cyberloafing on employee performance. A quantitative research method was employed, with data collected through questionnaires distributed to 69 respondents. The data were analyzed using multiple linear regression tests to determine both partial and simultaneous effects. The results indicate that, partially, work discipline and workload have a significant influence on employee performance, while cyberloafing has no significant effect. Simultaneously, all three variables have a joint impact on performance. These findings suggest that effective management of employee discipline and workload can enhance performance levels, whereas controlling cyberloafing behavior helps maintain productivity and work focus. Practically, this research contributes to the formulation of strategic human resource policies that can increase efficiency, optimize task distribution, and reduce unproductive online behavior among government employees.